2018
DOI: 10.3390/polym10111231
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Chain Mobility under Shear—A Rheo-NMR Investigation

Abstract: The local dynamics in polymer melts and the impact of external shear in a Couette geometry have been investigated using rheological nuclear magnetic resonance (NMR). The spin-spin relaxation time, T2, which is sensitive to chain-segment motion, has been measured as a function of shear rate for two samples of poly(dimethylsiloxane). For the low-molecular-weight sample, a mono-exponential decay is observed, which becomes slightly faster with shear, indicating restrictions of the polymer chain motion. For the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Strong dipolar coupling in rigid samples induces faster decoherence, while in samples with high molecular mobility, T 2 can be longer as the process is less efficient. In polymeric systems, greater entanglements and/or cross-linking density results in a decrease in mobility that manifests as shorter T 2 values. , In Figure , we illustrate the T 2 values collected for these 12 samples as a function of RH and CO 2 exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong dipolar coupling in rigid samples induces faster decoherence, while in samples with high molecular mobility, T 2 can be longer as the process is less efficient. In polymeric systems, greater entanglements and/or cross-linking density results in a decrease in mobility that manifests as shorter T 2 values. , In Figure , we illustrate the T 2 values collected for these 12 samples as a function of RH and CO 2 exposure.…”
Section: Resultsmentioning
confidence: 99%
“…In polymeric systems, greater entanglements and/or cross-linking density results in a decrease in mobility that manifests as shorter T 2 values. 65,66 In Figure 4, we illustrate the T 2 values collected for these 12 samples as a function of RH and CO 2 exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Concurrent steady or dynamic rheological measurements and time-domain NMR spectroscopy can provide information about the relationship between the polymer mobility, orientation, or crystallization and sample deformation or mechanical properties. For example, shear induced changes in entanglement dynamics, shear history effects on crystallization, and polymer–inorganic filler interactions and their effect on crystallization have all been characterized through rheo-NMR techniques. Rheo-NMR has many potential applications in the study of reversible gels to understand the coupling between macroscopic mechanical deformation and molecular cross-linking and dynamics. For example, rheo-NMR has shown that shear reduces the intermolecular linkages between κ-carrageenan, a seaweed extract that undergoes thermoreversible gelation in solution and is used as a polysaccharide thickener in the food industry …”
Section: Network Mechanics and Dynamicsmentioning
confidence: 99%
“…In polymeric systems, greater entanglements and/or crosslinking density results in a decrease in mobility that manifests as shorter T 2 values. 62,63 In Figure 5, we illustrate the T 2 values collected for these twelve samples as a function of RH and CO 2 exposure. Performing an inverse Laplace transform on the T 2 echo train decay curves produces relaxation spectra (plotted in Fig.…”
Section: Nmr Mobile Universal Surface Explorer (Mouse)mentioning
confidence: 99%